2010
DOI: 10.1002/path.2686
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profiling of gastric carcinoma in situ and adenomas by array‐based comparative genomic hybridization

Abstract: Although genomic copy number aberrations (CNAs) of gastric carcinoma at the advanced stage have already been extensively characterized by array comparative genomic hybridization (array CGH) analysis, those of gastric carcinoma in situ (CIS) are still poorly understood. Furthermore, no reports have demonstrated correlations between CNAs and histopathological features of gastric adenoma. In this study, we investigated CNAs of 20 gastric CISs (Vienna category 4.2) and 20 adenomas including seven low-grade adenoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 42 publications
7
22
0
Order By: Relevance
“…Both lineages could have derived from a common trunk with 8q+, 13q+, 20p/q+, and 5q−, commonly detected in both cluster A and cluster B. These findings partly confirm the report of Uchida et al [18], who reported 8p± and 5q− as early changes of GC, and then cluster-specific later changes, such as 7pq+ in cluster A and 4pq− in cluster B (Fig. 4).…”
Section: Discussionsupporting
confidence: 82%
“…Both lineages could have derived from a common trunk with 8q+, 13q+, 20p/q+, and 5q−, commonly detected in both cluster A and cluster B. These findings partly confirm the report of Uchida et al [18], who reported 8p± and 5q− as early changes of GC, and then cluster-specific later changes, such as 7pq+ in cluster A and 4pq− in cluster B (Fig. 4).…”
Section: Discussionsupporting
confidence: 82%
“…Several studies have revealed that genetic alterations begin in the early stages of cancer and even in precancerous lesions. Early studies using CGH arrays suggested that an 8q gain in HGIN may play a pivotal role in the development of gastric carcinoma [7] . However, the gene expression levels and functions associated with the copy number status of 8q were not detailed.…”
Section: Var1mentioning
confidence: 99%
“…Based on the potential transition between and morphological similarity of dysplasia and carcinoma, the hypothesis that they are biologically related is reasonable. Previous studies of the genomic copy number aberration of gastric precancerous lesions and carcinoma in situ (CIS) have provided the most prominent 8q gain, which was detected most frequently in both HGIN and CIS but was undetected in LGIN using array comparative genomic hybridization [7] . Therefore, evidence has shown that molecular variations in gastric carcinogenesis have already appeared in precancerous lesions or EGC.…”
Section: Introductionmentioning
confidence: 99%
“…Most frequent losses of the copy number at 5q22 in GC patients of difference racial are summarized in Table S1 in File S1 [8][10], [12], [13], [17]–[22]. Studies reported that 15.4% in Japanese [10], 35% in Korean [21], and 21% in Turk [20] of GC patients had gene mutations at 5q14–22.…”
Section: Introductionmentioning
confidence: 99%